The impact of a disparity-reduction intervention on outcomes of patients with acute coronary syndrome in the emergency department: a clinical trial - Mehdi Moradinia; Sajad Yarahmadi; Mehdi Birjandi; Mohammad Gholami (International Journal for Equity in Health)
Abstract Background Patients with acute coronary syndrome (ACS) who belong to marginalized groups often do not receive equitable treatment and care when they are referred to emergency departments (ED), and this can have negative consequences for these patients. Therefore, this study aimed to evaluate the impact of a disparity-reduction intervention on outcomes of patients with ACS in the ED. Methods This randomized clinical trial included 264 ACS patients, randomly allocated into intervention (n = 132) and control group (n = 132). The intervention involved improving the triage process by (1) welcoming nurses and (2) conducting specialized triage. Also, a patient navigation (PN) program was implemented, comprising (1) emergency care comprehensive management, (2) supportive education and counseling, and (3) clinical actions with follow-up care. In the control group, standard triage and routine care were provided. Outcomes assessed included pain intensity, patient opinion of pain management, illness perception, threat perception, and short and long-term outcomes. Results The results showed that after the intervention, pain intensity and threat perception decreased significantly in the intervention group compared to the control group (P < 0.001). Moreover, the opinion of pain management—assessed only post-intervention—was significantly more favorable in the intervention group than in the control group (P < 0.001). Illness perception scores also increased more prominently in the intervention group than in the control group (P < 0.001). Short-term outcomes showed improvement in the intervention group compared to the control group (P < 0.05). Long-term outcomes revealed that the intervention group experienced better results than the control group in specialist visits, exercise stress tests, echocardiography, and readmissions (P < 0.05). Conclusion Interventions such as improving the triage process and the PN are important in reducing disparities and improving patient outcomes. These findings underscore the effectiveness of tailored strategies in promoting equitable care in ED.